Introducing Old Testament Theology : Creation Covenant and Prophecy in the Divine Human Relationship - Bellinger, W. H. (William H.), Jr., 1949- (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2022)
"A senior scholar and teacher offers a concise, student-level theology of the Old Testament"--
Includes bibliographical references (pages 181-187) and indexes
Keywords: Bible. -- Theology; Bible. -- Criticism, interpretation, etc; Old Testament Theology Prophecy -- Creation and Covenant -- Divine Human Relationship